Analisis Pendapatan Petani Kelapa Sawit Perkebunan Rakyat di Nagari Talao Sungai Kunyit Kecamatan Sangir Balai Janggo Kabupaten Solok Selatan - Randi Satria; Amnilis; Gusriati (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to determine the income of smallholder oil palm farmers and analyze the factors that influence these incomes in Nagari Talao Sungai Kunyit. This research was conducted in September - October 2021. The research method used was descriptive quantitative. The population in this study is smallholder oil palm farmers who have a land area of 2 Ha, the age of the plant is between 5-25 years, and a minimum of 5 years of experience. The population is 173 farmers and the sample is 63 people. Data analysis used income analysis and multiple linear regression analysis using SPSS version 20. The results showed that the income of smallholder oil palm farmers in Nagari Talao Sungai Kunyit was Rp. 1,580,328/Ha/Month. The factors that partially have a significant effect on the income of smallholder oil palm farmers in Nagari Talao Sungai Kunyit are: land area, oil palm prices and labor costs. Meanwhile, those that have a significant effect simultaneously (simultaneously) are land area, oil palm price, fertilizer cost, plant age, number of family members, farming experience, and labor costs with a significant value of 0.000 < 0.005. The value of R square is 0.899.